Fraud Disclosure Tendency in Banking System: Impact of Psychological Contract Breach and Organizational Factors - Ali Sheikhi; Amin Nazemi (Iranian Journal of Accounting, Auditing & Finance)
This study addresses the impact of psychological contract breaches and organizational factors on fraud disclosure in the banking system. The statistical population includes all the employees and internal auditors in the banks listed on the stock exchange in 2022. The data is collected using a questionnaire. Structural equation modeling and Smart PLS v.3 Software propose and test eight hypotheses. Results showed a significant negative relationship between interpersonal effect, employee transactional relationship, financial system instability, deficient organizational changes, and unethical organizational morality with fraud disclosure. However, results showed no significant relationship between past disclosure responses and fraud disclosure tendency. The mentioned organizational factors affect fraud disclosure via the mediating role of psychological contracts. The last hypothesis showed that employees tend to disclose fraud to their supervisors rather than to the fraudster and internal auditors. This article is an innovative study because it is the first research addressing psychological contracts' effects in the accounting and auditing field. Our results and findings by investigating the negative impact of psychological contract breach on the tendency to disclose fraud contribute to audit literature, fraud diamond, and fraud disclosure. Psychological contract breach might affect the “opportunity” element in the fraud diamond by not whistleblowing fraud. Management relies on their employees as an internal control against fraud.